T-lymphocyte profile as a predictive marker for placental retention in buffalo (Bubalus bubalis) - SINGH, PRAHLAD; SHARMA, R D; NANDA, A S; SINGH, HARMEET (The Indian Journal of Animal Reproduction, 2023)
Peripheral blood lymphocyte profile was assessed in buffaloes with normal placental separation (n=5) and those with retention of placenta (n=5). Jugular venous blood samples (30 ml) were collected from every buffalo on 1 to 10 days pre partum, day of calving and on 1 to 10, 15, 20, 25 and 30 day post partum. T-Iymphocyte profile was evaluated, with respect to, per cent peripheral blood lymphocyte sheep red blood cell-rosettes (SRBC-R). Plasma vitamin-A, b-carotene, vitamin - E and zinc were estimated for every subject on the sampling days, by standard methods. Significant (P<0.01) differences in the mean values of SRBC-R per cent were observed between subjects with normal placental separation and those with retention across the respective days. SRBC-R per cent and plasma parameters indicated a steady decline from 10 to 1 day pre partum, the declination being significant (P<0.01) around 6 to 4 day pre partum till day of calving in both the groups, whereas, the values were significantly lower (P < 0.01) in affected group. Lower values persisted for 5 to 10 day post-partum in control group and for 20 to 25 day postpartum in affected group. Significant (P < 0.01) relationships between SRBC-R profile and plasma biochemical variables were seen. The overall effect of vitamin A, b-carotene, vitamin E and zinc was statistically significant (P < 0.01) in both the groups. The results suggest that better the initial state of health of the buffaloes, in terms of their SRBC-R status, better the pregnancy outcome. Thus concluding that retention of placenta is associated with abnormally low levels of peripheral blood T-Iymphocyte levels at calving. Also that the pre partum lower (P<0.01) TIymphocyte profile in retention cases may serve as an index of retention of fetal membranes in buffaloes.